DEFINING THE HYPNOSIS FROM THE PSYCHOBIOLOGY: SOME LINES OF SCIENTIFIC DEVELOPMENT OF THE HYPNOTICS PHENOMENA - Juan Cristóbal Ruiz Díaz; Guy Santibáñez-Hidalgo (CAEN, 2008)
In the present article we defined hypnosis from a psychobiologic viewpoint. We understand this phenomenonas a particular "global state" in which the subject exhibit changes both in subjective - conscious state - and invisceral, automatic and behavioural process, al these as a result of integrative activity of the neuro-endocrinesystem (NES). Here we petend two objetives, the first: to outline a preliminar definition of hypnosis as a state,and the second: present a review of some neuroscientific studies about different hypnotic phenomena. Withinthe hypnotic phenomena, we select five of them of general interest: pain, perceptual modulation, emotionalevocation, phobia treatment and attentional conflict manegment in hipnosis. These are relevant due they may contribute unto a vast development in basic investigation and in aplied psychotherapy. Phobia investigation has demonstrate the positive effect in patients highly hypnotizable, this treatment aloud to restore the sympatic-vagal balance. The brain imaging results suggest an attentional change model, in which participate the anterior cingulate cortex (ACC). Emotional control studies stablished changes in evoqued potential in different cortical regions. The hypnosis posibillities to inhibit and to evoke emotions in front of specific virtual events are of enormous value in therapy. Attentional studies present the effect of specific suggestions in higly hipnotizable patients, the activity of ACC and visual cortex decrease significatively. These outcomes correlate with a lessen attentional conflict (attentional interference) during Stroop paradigm. All these findingsdemonstrate that hypnosis is a productive field for basic and clinical investigation.